Serum Anti-Apo B Antibody Level as Residual CVD Marker in DM Patients under Statin Treatment - Imai, Minami; Murata, Yukie; Suzuki, Toshinobu; Kihara, Shinji; Hashimoto, Kunihiko; Kawamura, Mari; Kochi, Ikoi; Yamamoto, Hiroyasu; Chen, Yingchao (Journal of Atherosclerosis and Thrombosis, 2019)
Aim: In the pathogenesis of atherosclerosis, autoantibodies have two-facedness of progression and protection. Previous reports have indicated that low autoantibody levels against apolipoprotein B-100 (apo B-100) could increase the risk of atherosclerotic cardiovascular diseases (CVD) in healthy subjects. In this study, we investigated the relationship between circulating anti-apo B-100 autoantibodies and the clinical parameters in Japanese diabetic patients with or without CVD.Methods: We measured the serum levels of anti-apo B-100 autoantibodies against native and malondialdehyde (MDA)-modified p45 or p210 epitopes, as well as anti-apo E autoantibodies, using enzyme-linked immunosorbent assay.Results: In patients with CVD, the circulating levels of IgG against native p45, MDA-modified p45, and MDA-modified p210 (IgGN-45, IgGMDA-45, and IgGMDA-210) were significantly lower than those in patients without CVD, whereas no difference was observed in anti-apo E autoantibody levels. In addition, IgMN-45, IgMMDA-45, and IgGMDA-45 were negatively correlated with LDL-C levels, whereas IgGN-45 and IgGN-210 were positively correlated with HbA1c levels. No correlation was observed between autoantibody levels and diabetic microangiopathy. In the statin-treated subgroup, IgGMDA-45 and IgGMDA-210 were significantly lower in patients with CVD than in those without CVD.Conclusion: Measurement of serum anti-apo B-100 autoantibodies can be useful for the evaluation of CVD risk in patients with diabetes receiving statin treatment.